In quest of reducing the environmental impacts of food production and consumption. (1st January 2017) - Sala, Serenella; Anton, Assumpcio'; McLaren, Sarah J.; Notarnicola, Bruno; Saouter, Erwan; Sonesson, Ulf
Abstract: Food supply chains are increasingly associated with environmental and socio-economic impacts. An increasing global population, an evolution in consumers' needs, and changes in consumption models pose serious challenges to the overall sustainability of food production and consumption. Life cycle thinking (LCT) and assessment (LCA) are key elements in identifying more sustainable solutions for global food challenges. In defining solutions to major global challenges, it is fundamentally important to avoid burden shifting amongst supply chain stages and amongst typologies of impacts, and LCA should, therefore, be regarded as a reference method for the assessment of agri-food supply chains. Hence, this special volume has been prepared to present the role of life cycle thinking and life cycle assessment in: i) the identification of hotspots of impacts along food supply chains with a focus on major global challenges; ii) food supply chain optimisation (e.g. productivity increase, food loss reduction, etc.) that delivers sustainable solutions; and iii) assessment of future scenarios arising from both technological improvements and behavioural changes, and under different environmental conditions (e.g. climate change). This special volume consists of a collection of papers from a conference organized within the last Universal Exposition (EXPO2015) "LCA for Feeding the planet and energy for life" in Milan (Italy) in 2015 as well as other contributions that were submitted in the year after the conference that addressed the same key challenges presented at the conference. The papers in the special volume address some of the key challenges for optimizing food-related supply chains by using LCA as a reference method for environmental impact assessment. Beyond specific methodological improvements to better tailor LCA studies to food systems, there is a clear need for the LCA community to "think outside the box", exploring complementarity with other methods and domains. The concepts and the case studies presented in this special volume demonstrate how cross-fertilization among difference science domains (such as environmental, technological, social and economic ones) may be key elements of a sustainable "today and tomorrow" for feeding the planet. Highlights: Life cycle thinking represents a reference method for assessing agro-food supply chains. LCA should be improved towards better assessing sustainability questions related to food systems. This special volume illustrates challenges and pathways for improving food supply chains. Food waste management, nutrient recovery, and resource efficiency are at the hearth of sustainability of food systems. Complementing LCA with other methods and scientific domains is more and more needed.